2014
DOI: 10.1111/clr.12472
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia with laser‐modified microgrooved surface vs. titanium implants covered with melatonin stimulates bone formation. Experimental study in tibia rabbits

Abstract: Within the limitations of this pilot study in rabbits, we can conclude that the local application of melatonin increases the BIC values in titanium and in zirconia implants at 1 week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…The results revealed that melatonin treatment significantly inhibits regional resorption of alveolar bone and contributes to periodontal healing in this experimental periodontitis rat model . Moreover, several published reports indicate that melatonin stimulates bone formation …”
Section: Prospects and Conclusionmentioning
confidence: 62%
“…The results revealed that melatonin treatment significantly inhibits regional resorption of alveolar bone and contributes to periodontal healing in this experimental periodontitis rat model . Moreover, several published reports indicate that melatonin stimulates bone formation …”
Section: Prospects and Conclusionmentioning
confidence: 62%
“…The use of melatonin to promote bone regeneration in dental implant placement was assessed in several studies, based on different animal models in which the authors employed melatonin alone or in combination with other substances, such as, growth hormone or porcine bone [2,40,41,42,43,44,45,46,47]. The studies using melatonin to promote dental implant stability evaluated in this review are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…These findings agree with those obtained in implants placed in rabbit tibia, where the presence of well-remodelled cortical bone and new fronts of osteoblasts could be observed in animals treated with melatonin compared to the control group [44,46], as well as increased trabecular, but not cortical BIC. The effect of melatonin in zirconia implants was studied by the group of Calvo-Guirado [47], obtaining better results at one and four weeks in the treated implants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of submerging titanium and zirconia implants in a 5% melatonin solution on the BIC after an insertion period of 1 and 4 wk was also investigated . Both titanium and zirconia implants showed a significantly higher BIC at the early (1 wk) time point (titanium, 29.7 ± 2.4 %; zirconia, 28.9 ± 1.3 %; p < 0.05).…”
Section: Resultsmentioning
confidence: 99%